Urbanization and child growth failure in Sub-Saharan Africa: A geographical analysis - Ru, Yating; Haile, Beliyou; Caruthers, John I. (Springer, 2022)
This paper raises a fundamental question about Sub-Saharan Africa: has urbanization there been accompanied by improvements in personal wellbeing? It then proceeds to open an investigation focused on child health—in the form of child growth failure, including (i) stunting; (ii) wasting; and (iii) underweight—that addresses the question. The main contribution of the work is to reconcile an array of data, collected across different spatial scales and over different timeframes, in a manner that enables some preliminary insight into the relationships explored. Evidence derived from the analysis suggests that the wave of urbanization breaking across Sub-Saharan Africa is associated with improvements in wellbeing, a finding that is qualified by need for further research.